The Effect of Company Characteristics on Anti-Corruption Disclosure in Mining Sector Companies Listed on the Indonesia Stock Exchange - Rahmawati, Novia Ayu; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
The purpose of this study is to examine the influence of company size, industry type, and international operations on anti-corruption disclosure in mining sector companies listed on the Indonesia Stock Exchange in 2020 - 2022. The sample of this study was selected using the purposive sampling method. The study looked at 14 companies. This study uses SPSS software version 26 as the calculation tool. Based on this study, the results show that the size of the company, the type of industry, and the international operation have no influence on anti-corruption disclosure. The predictive ability of the three variables on anti-corruption disclosure is 15% while the others are 85%.